Pengujian Penerapan Layanan Sistem Informasi Pada Dinas Perhubungan Menerapkan Metode DeLone and McLean - Hizbi Muhammad Yazdi; Resad Setyadi; Sarah Astiti (STMIK Budi Darma, 2022)
The Motor Vehicle Testing Information System (SIMPKB) is an Information System (SI) for the implementation of periodic vehicle tests that are used to improve the quality of public transportation. The Brebes Regency Transportation Service has a vehicle periodical testing unit for the Pekalongan residency area. The implementation of the test focuses on providing services to the community by periodically testing the feasibility of motorized vehicles. The problem that occurs is that there are still obstacles in the use of the system and the lack of a document for evaluating the performance of system services whether the system is suitable for use from the organization and user perspective. This study aims to determine the extent to which the success rate of implementing SIMPKB services. This research method uses quantitative methods using the DeLone and McLean model of measurement. Data collection method by analyzing questionnaires from respondents using SmartPLS. The results of this study user satisfaction has a value of 0.765, it can be said that it is influenced by the construct of system quality, service quality and information quality by 76.5%. Meanwhile, having an value of 0.745, it can be interpreted that the validity of the construct of Use (P) can be said to be influenced by the construct of system quality, service quality and information quality is 74.5%. From the 7 hypotheses, only system quality and service quality greatly affect user satisfaction and the use of the Motor Vehicle Testing Information System (SIMPKB) at the Brebes Regency Transportation Service